PENGARUH NILAI PERUSAHAAN, SALES GROWTH, DAN LEVERAGE TERHADAP FINANCIAL DISTRESS (STUDI KASUS PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI PERIODE 2021 – 2024) - Rosalinda Ayu Prameswari; Istiono Istiono (Jurnal Ekonomi dan Bisnis, 2026)
This study aims to analyze the influence of firm value, sales growth, and leverage on financial distress in manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2021-2024 period. This study used a quantitative approach with secondary data in the form of annual financial reports obtained from the official Indonesia Stock Exchange website. The sampling method used a purposive sampling technique to obtain a number of manufacturing companies that met the research criteria. Data analysis was performed using multiple linear regression with the help of SPSS Version 25. The results show that simultaneously, firm value, sales growth, and leverage significantly influence financial distress. Partially, firm value significantly influences financial distress, indicating that the higher the firm value, the lower the likelihood of a company experiencing financial difficulties. Leverage also significantly influences financial distress, as high debt levels increase the risk of financial distress. Meanwhile, sales growth did not significantly influence financial distress, indicating that sales growth does not always reflect a company's financial condition if it is not accompanied by sound cost management and funding structure.The results show that simultaneously, firm value, sales growth, and leverage significantly influence financial distress. Partially, firm value significantly influences financial distress, indicating that the higher the firm value, the lower the likelihood of a company experiencing financial difficulties. Leverage also significantly influences financial distress, as high debt levels increase the risk of financial distress. Meanwhile, sales growth did not significantly influence financial distress, indicating that sales growth does not always reflect a company's financial condition if it is not accompanied by sound cost management and funding structure